A promising fruit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Fruits such as the orange, papaya and tamarind have travelled the world so much that one could easily forget where they originally came from (China, Mexico and Sudan, respectively). Perhaps the Mangabeira (Hancornia speciosa) from Brazil will follow...